2020
DOI: 10.1039/d0ra00142b
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for preparing non-fluorescent graphene oxide quantum dots as fluorescence quenchers in quantitative real-time PCR

Abstract: In recent years, graphene oxide quantum dots (GOQDs) have emerged as novel nanomaterials for optical sensing, bioimaging, clinical testing, and environmental testing. However, GOQDs demonstrate unique photoluminescence properties, with GOQDs having quantum limitations and edge effects that often affect the accuracy of the test results in the sensory field. Herein, GOQDs with a large content of hydroxyl groups and low fluorescence intensity were first prepared via an improved Fenton reaction in this study, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…primers) through π-π stacking and hydrogen bonding, thereby allowing the matched primer-template complexes to be detached from its surface for subsequent PCR reactions, while the primers remain adsorbed on its surface when mismatched. The above findings encouraged our group to introduce in 2019 GOQDs into the qRT-PCR system to improve its performance [ 161 ]. GOQDs can adsorb primers and TaqMan probes by π-π stacking and hydrogen bonding, thereby reducing the background fluorescence intensity of TaqMan probes, reducing the non-specific amplification in PCR reactions and improving the specificity of the detection.…”
Section: Nucleic Acid Amplification Technologiesmentioning
confidence: 99%
“…primers) through π-π stacking and hydrogen bonding, thereby allowing the matched primer-template complexes to be detached from its surface for subsequent PCR reactions, while the primers remain adsorbed on its surface when mismatched. The above findings encouraged our group to introduce in 2019 GOQDs into the qRT-PCR system to improve its performance [ 161 ]. GOQDs can adsorb primers and TaqMan probes by π-π stacking and hydrogen bonding, thereby reducing the background fluorescence intensity of TaqMan probes, reducing the non-specific amplification in PCR reactions and improving the specificity of the detection.…”
Section: Nucleic Acid Amplification Technologiesmentioning
confidence: 99%
“…Reprinted from [76] with permission from the American Chemical Society. Xiao and He et al [77] fabricated GOQDs (G20) for the detection of DNA sequences (Figure 22). Briefly, G20 was treated with three different fluorescent dyes to check the photoluminescence properties and quenching effect.…”
Section: Dna and Rna Sensormentioning
confidence: 99%
“…Graphene oxide (GO) is an oxidized form of graphene that contains numerous oxygen-containing functional groups on its surface because of the powerful effects of certain oxidizing agents, which render GO hydrophilic and biocompatible for a wide range of biomedical applications. Previous studies have demonstrated that GO could adsorb single-stranded DNA through π–π stacking and hydrogen bonding, while dsDNA bases were shielded by negatively charged phosphate groups and had a low affinity for GO. The use of GO in the PCR system can promote the formation of primer–template complexes and accelerate PCR rates. A previous study has reported on the introduction of graphene oxide quantum dots into the qRT-PCR system to improve its performance . In another study, a newly established GO-based qRT-PCR method was used to detect ovarian cancer-associated miRNAs .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has reported on the introduction of graphene oxide quantum dots into the qRT-PCR system to improve its performance. 35 In another study, a newly established GO-based qRT-PCR method was used to detect ovarian cancer-associated miRNAs. 36 GO was further used in qRT-PCR, and it was found that the pre-adsorption of primers onto the GO surface could improve the efficiency of primer−template hybridization and reduce nonspecific amplification, thus improving the sensitivity of qRT-PCR.…”
Section: ■ Introductionmentioning
confidence: 99%